Multisite pain in adolescents and the association with ACE - Falch, Aurora (UiT Norges arktiske universitet, 2022)
Background: Both children and adolescents often express musculoskeletal pain without a clear somatic cause. The prevalence of musculoskeletal pain has been shown to be increasing. Additionally, there has been described a sharp rise in prevalence of so-called adverse childhood experiences (ACE), and studies have shown that musculoskeletal pain may be related to different ACE. The aim of this study was to evaluate possible associations between multisite musculoskeletal pain and ACE. Method: The Norwegian Arctic Adolescent Health Study (NAAHS) was conducted among 10th graders (15–16-year old’s) in the two northernmost counties in Norway during 2003-2005. Univariate analyses were carried out using descriptive statistics; Chi-square tests and one-way ANOVA. Hierarchical, linear multiple regression was used for the multivariable analysis examining the relationship between multisite musculoskeletal pain and adverse life events. Results: We found a high prevalence of both musculoskeletal pain and adverse life events among the adolescents and the prevalence of both factors were especially high for females. We found a linear relationship between the increasing prevalence of adverse life events and increasing number of musculoskeletal pain sites, especially for females. In the multivariable analysis adverse life events was not significantly associated with musculoskeletal pain, and psychosocial factors had a mediating effect on the relationship. Conclusion: Our study suggests an important association between the extent of ACE and the experience of multisite musculoskeletal pain in adolescents. Our findings emphasize the importance of early intervention and treatment when it comes to ACE.